Influence of Dosages of Biofertilizers Composed of Mycorrhizae and Diazotrophs on the Corn Productivity - Jordan Joao Palacios Zambrano; Vianka Stéfany García García (ESPOCH Congresses, 2021)
Abstract Corn (Zea mays L.) is a crop of world importance, however, one of the problems present during its development is the lack of nutrients or the presence of these in a form not available to the plant. Because of this, the objective of this review article is to gather information on the influence of different dosages of mycorrhiza and diazotroph biofertilizers on the corn crop. A meticulous bibliographic research was carried out, detailing the methods used by various authors; Among the most repetitive and significant factors are the use of mycorrhizae and nitrogen-fixing bacteria plus fertilization with P, the following treatment stands out: 200 gr ha - 1 (using mycorrhizae and nitrogen-fixing bacteria); the common response variable of the authors mentioned in methodology was grain yield. The results obtained by the majority of authors show that grain yield improves significantly in the interaction of mycorrhizae and diazotrophs plus chemical fertilization; As a result of the aforementioned treatment, the yield of corn kg ha - 1 was increased by 37%, by virtue of these results it is concluded that the most appropriate thing would be to take it into account to apply it on the corn crop.